2-D gel densitometer for high-contrast and selective imaging of chlorophyll-containing protein complexes separated by non-denaturing polyacrylamide gel electrophoresis - Ilík, Petr; Krchnák, Pavel; Tomek, Pavel; Naus, Jan (Journal of biochemical and biophysical methods, 2002)
In this work, we present a home-made two-dimensional (2-D) CCD imaging system for the monochromatic densitometry of plane gels and its application to the imaging and densitometry of chlorophyll (Chl)-containing proteins separated by non-denaturing polyacrylamide gel electrophoresis. The monochromatic imaging of separated green bands at the wavelengths corresponding to their absorption band increases their contrast. This allows a better visualization of the faint-green bands in the gel and using of samples with lower Chl content for the electrophoresis. By the comparison of 2-D densitograms of the same gel illuminated with 670 and 650 nm lights, that is, at the red absorption maximum of Chl a and b, respectively, we achieved a selective imaging of the complexes with different Chl a/b ratio. This approach was used to specify an unknown band that appeared in the gel of the sample prepared from the thylakoid membranes of preheated barley leaves.
Keywords: chlorofyl; Electrophoresis, Polyacrylamide Gel; ječmen (rod); 2D gelová elektroforéza; Hordeum; Photosynthetic Reaction Center Complex Proteins; světlosběrné proteinové komplexy; elektroforéza v polyakrylamidovém gelu; fotosyntetická reakční centra (proteinové komplexy); Chlorophyll; Electrophoresis, Gel, Two-Dimensional; Light-Harvesting Protein Complexes